AB0612 Multicenter Registry on Inflammatory Myopathies in Madrid (REMICAM): Descriptive Analysis. (15th July 2016) - Nuño, L.; García, M.J.; Lόpez Longo, F.J.; Maldonado, V.; Llorente, I.; Barbadillo, C.; García de la Peña, P.; Ruiz, L.; Moruno, H.; Cobo, T.; Almodovar, R.; Lojo, L.; et al.
Abstract : Background: Clinical manifestations, evolution and prognosis of idiopathic inflammatory myopathies (IIM) are very heterogeneous which, together with its low prevalence, limits the study of the disease. Objectives: To analyze the clinical characteristics of patients diagnosed of IIM in a multicenter study. Methods: A multicenter retrospective descriptive study from REMICAM 1 myositis study group was performed. All patients were diagnosed with IIM according to Bohan and Peter 2 criteria, were followed up sometime between January 1980 and December 2014 and were classified into 7 different clinical subgroups: primary dermatomyositis (DM), primary polymyositis (PM), juvenile dermatomyositis (JuvM), cancer associated myositis (CAM), overlap myositis (OM), inclusion body myositis (IBM) and necrotizing myositis (NM). Results: 478 IIM cases were included. 74% of the cases was women, with an age at diagnosis of 43.7±22.6 years, and an average follow-up time of 9.7±8.3 years. The main IIM subgroups were primary myopathies (PM 28%, DM 22%, OM 19.9%, JuvM 19.2%, CAM 8.4%, NM 1.3%, BMI 1.3%). The connective tissue diseases more frequently associated in OM subgroup were MCTD (30%), systemic sclerosis (27%) and SLE (18, 9%). The main extramuscular manifestations were cutaneous lesions (65%), arthritis (43%), general symptoms (39%) gastrointestinal complications (33%), and interstitial lung disease (ILD) (30%). Patients with OM had a higher prevalence of ILD (46.8% vs. 25.8%;p<0.001), Raynaud (67% vs. 19.4%;p<0.001), arthritis (70% vs. 35.8%;p<0.001) and cytopenias (55.9% vs. 21.5%; p<0.001), whereas JuvM patients developed more calcinosis (30.4% vs. 5.7%;p<0.001) but fewer serious infections (4.7% vs. 29.3%;p<0.001). During the period of study 114 patients died (24%), and the main causes of death were infections (24%), cancer (24%) and cardiovascular events (22%). Conclusions: In this multicenter REMICAM registry 478 IIM cases have been included. The most common subtypes were primary myopathies, and the most frequent extramuscular manifestation were typical cutaneous lesions. Overlap myositis patients presented with more extramuscular manifestations than the other subgroups. References: REMICAM: Registry on inflammatory myopathies from Madrid Bohan A, Peter JB. N Engl J Med 1975 Feb 13;292(7):344–7. Disclosure of Interest: None declared